2008
DOI: 10.1016/j.molcel.2008.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Extraproteasomal Rpn10 Restricts Access of the Polyubiquitin-Binding Protein Dsk2 to Proteasome

Abstract: Summary Polyubiquitin is a diverse signal both in terms of chain length and linkage type. Lysine48-linked ubiquitin is essential for marking targets for proteasomal degradation but the significance and relative abundance of different linkages remain ambiguous. Here we dissect the relationship of two proteasome-associated polyubiquitin-binding proteins, Rpn10 and Dsk2, and demonstrate how Rpn10 filters Dsk2 interactions, maintaining proper function of the ubiquitin-proteasome system. Using quantitative mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(134 citation statements)
references
References 62 publications
7
127
0
Order By: Relevance
“…The latter is supported by the observation that, in both Drosophila (Haracska and Udvardy, 1995) and yeast (van Nocker et al, 1996), some of the proteasomal polyubiquitin receptors are found in a proteasome-unassociated pool. The presumed extraproteasomal role of Rpn10 and its extraproteasomal interaction with the Dsk2 polyubiquitin receptor are supported by the in vivo observation that the severe cytotoxicity of Dsk2 overexpression in yeast is mitigated by the accumulation of extraproteasomal Rpn10 (Matiuhin et al, 2008). The CTH of Rpn10, carrying the ubiquitin-interacting motif (UIM) is alone responsible for this compensatory function, suggesting that in its extraproteasomal state the UIM of Rpn10 might mask the UBL domain of Dsk2, competing in this way with the interaction of Dsk2 with the proteasome.…”
Section: Introductionmentioning
confidence: 92%
“…The latter is supported by the observation that, in both Drosophila (Haracska and Udvardy, 1995) and yeast (van Nocker et al, 1996), some of the proteasomal polyubiquitin receptors are found in a proteasome-unassociated pool. The presumed extraproteasomal role of Rpn10 and its extraproteasomal interaction with the Dsk2 polyubiquitin receptor are supported by the in vivo observation that the severe cytotoxicity of Dsk2 overexpression in yeast is mitigated by the accumulation of extraproteasomal Rpn10 (Matiuhin et al, 2008). The CTH of Rpn10, carrying the ubiquitin-interacting motif (UIM) is alone responsible for this compensatory function, suggesting that in its extraproteasomal state the UIM of Rpn10 might mask the UBL domain of Dsk2, competing in this way with the interaction of Dsk2 with the proteasome.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, the protease activity of Ddi1 could possibly provide an alternative to the proteasome as a means to attack ubiquitylated proteins. Dsk2 is distinguished by the existence of an extraproteasomal pool that is largely complexed to a free pool of Rpn10 (van Nocker et al 1996;Matiuhin et al 2008;Zhang et al 2009a). In this complex, the UBL domain of Dsk2 binds the UIM element of Rpn10, which is the ubiquitin-binding element of Rpn10 (Zhang et al 2009a).…”
Section: Regulatory Particlementioning
confidence: 99%
“…Interestingly, the UBL-UIM interaction can be displaced by a substrate-bound ubiquitin chain to form a ternary complex, that, with an unoccupied Dsk2 UBL domain, is activated for proteasome binding. Despite this interaction, Dsk2 does not bind proteasomes via Rpn10 (Elsasser et al 2002;Matiuhin et al 2008). Interestingly, a mammalian homolog of Dsk2 has been implicated in amyotrophic lateral sclerosis (Deng et al 2011).…”
Section: Regulatory Particlementioning
confidence: 99%
“…Growth arrest of yeast and the accumulation of large amount of polyubiquitinated proteins in cells are caused by overexpression of wild-type Dsk2 in yeast [7,17], which seem to be involved in Dsk2 function in the ubiquitin-proteasome pathway. When the effect of ubiquitin chains on the Dsk2-mediated growth arrest was examined, overexpressed Dsk2-KR failed to inhibit the growth as expected (Fig.…”
Section: Dsk2 Ubiquitination Affects In Vivo Ubiquitin-dependent Protmentioning
confidence: 99%
“…The Dsk2 UBA in cells binds preferentially to K48-chains of polyubiquitinated substrates [7,17]. It is reasonable that UBL-UBA proteins undergo a conformation change between 'open' and 'closed' forms [16].…”
Section: Dsk2 Uba Domain May Bind Alternatively Ubiquitin Chains Of Tmentioning
confidence: 99%